The Influence of Workload and Stress on Employee Performance in PT X Palm Oil Mill - Nidya Wisudawati; Dodi Aprianto Pratama (Publisher Cv. Inara, 2021)
The aim of this study was to determine the effect of employee workload and stress on the production process at PT X palm oil mill with a capacity of 600 tons/day. The process in this palm oil mill are broadly divided into 6 parts through several processing stations namely reception, treshing, stirring and pressing, clarification and nut and kernel stations. Work activities carried out with a standing attitude for a long time, monotonous, exposed to noise from production machines and the number of extra hours will have an impact on workload and work stress felt by employees. This study uses multiple linear regression analysis with 32 respondents. The results showed that workload and work stress simultaneously had a positive and significant effect on employee performance. Partially the workload has a positive and significant effect, while work stress does not significantly influence the performance of employee.